Manusia Satu Dimensi di Bangku Sekolah: Analisis Teori Kritis Herbert Marcuse terhadap Pendidikan yang Menjinakkan - Laily Divia Amlati; Khumairo Wardatul Jannah; Rizqi Dwi Cahyati; Jakaria Umro (STIKes Ibnu Sina Ajibarang, 2026)
Education is fundamentally a vehicle for human emancipation; however, contemporary school institutions often shift their function into pragmatic instruments of ideological domestication. This study aims to analyze the domestication of students' critical thinking in schools through the lens of Herbert Marcuse's Critical Theory on the